(untitled) (Research, Society and Development, 2020)
Introduction: Newborns and infants have anatomical and physiological disadvantages that interfere with adequate pulmonary function, associated with congenital heart diseases, this disadvantage can be accentuated, especially in cases where the treatment of choice is surgical. Postoperative physiotherapy offers strategies for pulmonary reexpansion and to alleviate surgical complications, in order to improve respiratory function. Objective: To carry out an integrative literature review about the physical therapy techniques of pulmonary reexpansion in the postoperative period of congenital heart surgery in newborns and infants, due to the scarcity of articles in the literature that explain the real function and importance of physical therapy in the postoperative period of cardiac surgery congenital in newborns and infants. Methodology: An electronic search was carried out in the BVS, CAPES, PEDro, PUBMED, SciELO and SCIENCE databases on physical therapy techniques for pulmonary reexpansion in the postoperative period of congenital cardiac surgery in this population. Results: 91 articles were selected in the integrative literature review, however, only 9 studies were in line with the theme and were included in this review, which state that physiotherapy improves lung function and reduces postoperative complications in newborns and infants undergoing cardiac surgery. Conclusion: Physiotherapy improves lung function and reduces postoperative complications in newborns and infants undergoing cardiac surgery. The secretion removal and pulmonary reexpansion techniques are effective for pulmonary reexpansion, however there is no technique considered to be the gold standard, and each patient must be evaluated individually.